GENDER, RELIGION AND PATRIARCHY: A SOCIOLOGICAL ANALYSIS OF CATHOLICISM AND PENTECOSTALISM IN NIGERIA - ATTOH, FRANCA CHITOH (Advances in Social Sciences Research Journal, 2017)
ABSTRACT The paper interrogates the nexus between gender, religion and patriarchy in a context where the marginalization of the female gender is continuous in spite of the strides in female education. The tension between religion and gender equality is a pervasive problem for orthodox Christianity despite its cardinal doctrine of equality of all beings before God. From the theistic doctrine the female gender is considered unequal, inferior and subordinate to the male gender and this is demonstrated in the roles assigned to the female gender in orthodox denominations. For instance in Catholicism, women cannot aspire to the position of the clergy but can join the religious order as reverend sisters or nuns. However, Pentecostalism has shown a remarkable reformation from orthodoxy by elevating women to the clergy as pastors and even bishops. Using data generated from a total of 15 key informants and deploying Karl Marx’s and Feminists postulations on religion the paper argues that Catholicism reinforces patriarchy through its role differentiation and complete closure to the female gender in the Church’s hierarchy. Pentecostalism on the other hand encourages female participation as clergy but there exists subtle reinforcement of patriarchy as no woman has ever held the position of General overseer within the top Pentecostal Churches. Key Words: Catholicism, Pentecostalism, Patriarchy, Gender and Religion.